A low-valence molybdenum-doped manganese iron lithium phosphate positive electrode material, a preparation method thereof and application thereof

CN122889746APending Publication Date: 2026-10-09NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611265555.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

第一,高价态掺杂易引发电荷补偿效应,为维持电中性,材料中部分Mn3+可能被还原为Mn2+,从而削弱Mn3+/Mn2+氧化还原对的容量贡献,降低实际比容量;

Benefits of technology

(1)本发明采用低价态钼(Mo3+)掺杂,Mo3+的离子半径(约0.069nm,六配位)与Mn2+(0.067nm)和Fe2+(0.061nm)更为接近,更容易进入晶格占据铁位和/或锰位,掺杂均匀性好。相比于高价态钼(Mo6+)掺杂,低价态钼掺杂不会引起剧烈的电荷补偿效应,有利于保持材料中Mn3+/Mn2+的氧化还原活性,充分发挥磷酸锰铁锂的高电压优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889746A_ABST
    Figure CN122889746A_ABST
Patent Text Reader

Abstract

The application discloses a low-valence molybdenum-doped manganese iron lithium phosphate positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion battery positive electrode materials. 1‑x‑y Mn x Mo y PO4 / C, wherein Mo is a low-valence molybdenum element, exists in the form of +3 valence in the material; 0.3<=x<=0.7, 0.005<=y<=0.05; the positive electrode material is coated with a carbon layer on the surface, and molybdenum ions occupy part of iron sites and / or manganese sites. The trivalent molybdenum is used to dope the manganese iron lithium phosphate, the ionic radius of the low-valence molybdenum ion is similar to that of Mn 2+ / Fe 2+ , lattice stable doping can be realized, meanwhile, the superexchange interaction between the low-valence molybdenum and Mn 3+ is utilized to synergistically inhibit the Jahn-Teller effect, and the structural stability and cycle performance of the material are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery cathode material technology, and particularly relates to a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, its preparation method and application. Background Technology

[0002] Lithium-ion batteries, with their high energy density and long cycle life, have become core energy storage components in portable electronic devices, electric vehicles, and energy storage systems. However, the balance between energy density, safety, and cost remains a key bottleneck restricting the industry's development. Cathode materials, as the core component determining the overall performance of the battery, directly affect its energy output, safety characteristics, and service life.

[0003] Lithium iron phosphate (LiFePO4) cathode materials are widely used due to their low cost, cycle stability, and high thermal safety; however, their operating voltage plateau is only about 3.4V, resulting in a relatively low energy density. Lithium manganese phosphate (LiMnPO4), on the other hand, has a high voltage plateau of about 4.1V and a theoretical energy density of about 701Wh·kg⁻¹. -1 However, it is limited by its extremely low intrinsic electronic conductivity and is prone to Mn dissolution and Jahn-Teller distortion during cycling, resulting in severe degradation of cycling stability and rate performance. Lithium manganese iron phosphate (LiMn) 1-x Fe x PO4 (LMFP) aims to combine the advantages of the two materials mentioned above, but it still cannot overcome the low electronic conductivity (10⁻⁶ Ω·cm). -9 ~10 -11 S / cm), sluggish one-dimensional diffusion kinetics of lithium ions, and Mn 3+ Inherent defects such as structural degradation caused by the induced Jahn-Teller effect.

[0004] To improve the electrochemical performance of LMFP, ion doping is considered one of the effective approaches. Its main mechanisms include: (1) introducing hetero ions to form lattice defects, regulating the electronic structure and reducing the band gap, thereby improving intrinsic electronic conductivity; (2) partially replacing transition metal sites, changing the local coordination environment, widening the lithium ion diffusion channel and reducing the migration activation energy; (3) using the charge compensation of high-valence ions or the lattice pinning effect of low-valence ions to suppress the synergistic expansion of Jahn-Teller distortion and enhance the toughness of the crystal structure.

[0005] There are currently reports of technologies using molybdenum doping to modify LMFPs, such as using MoO3 as the molybdenum source, and achieving doping through liquid-phase mixing, spray drying, and calcination. However, most existing schemes are based on high-valence molybdenum (MoO3). 6+ Doping, however, has the following prominent drawbacks in its technical approach: First, high-valence doping easily induces a charge compensation effect; to maintain electroneutrality, some Mn in the material... 3+ It may be reduced to Mn 2+ This weakens Mn 3+ / Mn 2+ The capacity contribution of redox pairs reduces the actual specific capacity; Second, Mo 6+ Ionic radius (approximately 0.059 nm for hexacoordinate) and Mn 2+ (0.067nm), Fe 2+ The difference (0.061nm) is significant. After doping, it is easy to induce local lattice distortion and internal stress accumulation, which endangers long-term cycling stability. Third, high-valence molybdenum sources (such as MoO3) have a low melting point (about 795℃) and volatilize significantly during high-temperature calcination, making it difficult to accurately control the actual doping amount and resulting in poor doping uniformity.

[0006] Furthermore, existing LMFP doping studies mostly focus on common elements such as Mg, Ti, Al, and V, while studies on low-valence rare metals (such as Mo) are less common. 3+ The doping modification of molybdenum ions has not been systematically studied. Compared with conventional doping elements, low-valence molybdenum ions exhibit unique electronic structures and chemical properties: their 4d... 3 In the electronic configuration, unpaired electrons can interact with Mn. 3+ 3D 4 Electron superexchange interactions hold promise for synergistically suppressing Jahn-Teller distortion through magnetic coupling; and Mo 3+ The ionic radius (approximately 0.069 nm) is similar to that of Mn. 2+ The high degree of matching results in minimal lattice distortion caused by doping; at the same time, the Mo-O bond has high covalent bond energy and bond strength, which is beneficial to enhancing the rigidity of the octahedral framework and improving structural stability.

[0007] In summary, there is currently a lack of cathode materials and their preparation methods that can effectively regulate the electronic structure through low-valence molybdenum doping, synergistically suppress the Jahn-Teller effect, and comprehensively optimize the capacity, cycle, and rate performance of LMFPs. New technical solutions are urgently needed to overcome the technical obstacles that prevent the simultaneous achievement of "capacity-cycle-rate" performance. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention proposes a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, its preparation method, and its applications. The aim is to utilize the doping control of low-valence molybdenum ions and their interaction with Mn... 2+ / Fe 2+ The similar ionic radius advantage enables lattice-stable doping, while the low-valence molybdenum ions and Mn... 3+ Superexchange interactions between Mn suppress Mn3+ The Jahn-Teller effect enhances the structural stability and electrochemical performance of materials.

[0009] To achieve the above objectives, the present invention provides the following technical solution: One objective is to develop a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, wherein the general chemical formula of the cathode material is: LiFe 1-x-y Mn x Mo y PO4 / C, wherein the low-valence molybdenum exists in the material in the form of +3 valence; 0.3≤x≤0.7, 0.005≤y≤0.05, and x+y<1; the surface of the cathode material is coated with a carbon layer; in the cathode material, molybdenum ions occupy part of the iron sites and / or manganese sites.

[0010] This invention utilizes low-valence molybdenum ions to dope lithium manganese iron phosphate, taking advantage of their reaction with Mn. 2+ / Fe 2+ Highly matched ionic radius (Mo 3+ Approximately 0.069 nm, Mn 2+ Approximately 0.067 nm), allowing dopant ions to smoothly enter the crystal lattice and stably occupy iron and / or manganese sites, forming a uniform substitutional solid solution, significantly reducing lattice distortion and internal stress accumulation, thereby improving the structural stability of the material. Simultaneously, low-valence molybdenum ions (with 4d...) 3 (electronic configuration) and Mn 3+ (3d) 4 The superexchange interaction between Mn and Mn can effectively and synergistically suppress Mn. 3+ The induced Jahn-Teller effect enhances the rigidity of the octahedral framework, preventing structural degradation during cycling. Furthermore, low-valence doping avoids the effects of high-valence doping (such as Mo). 6+ The charge compensation effect caused by ) will not reduce Mn 3+ Restored to Mn 2+ Thus, Mn was completely preserved. 3+ / Mn 2+ The capacity contribution of the redox pair fully leverages the material's high voltage advantage of approximately 4.1V. The surface-coated carbon layer further enhances interparticle electronic contact and reduces interfacial impedance, resulting in significant improvements in both electronic conductivity and lithium-ion diffusion kinetics.

[0011] Furthermore, in the general chemical formula, 0.4 ≤ x ≤ 0.6, 0.005 ≤ y ≤ 0.03.

[0012] Within this preferred composition range, the material achieves a better balance between capacity and rate performance. Example data clearly show that when the doping amount y=0.01, the material's 0.1C discharge capacity (166.04 mAh / g) and 1C discharge capacity (130.70 mAh / g) are significantly better than those with y=0.005 or y=0.015. This demonstrates that the present invention achieves optimal overall capacity-cycle-rate performance by optimizing the doping amount, verifying the effect of optimal doping amount.

[0013] Furthermore, the carbon layer comprises 1 to 10% of the total mass of the cathode material.

[0014] An appropriate amount of carbon coating can effectively improve the electronic conductivity between primary particles and reduce the interfacial contact resistance without excessively reducing the tap density of the material. This improves the capacity utilization of the material at high rates and the processing performance of the electrode, providing a good foundation for subsequent electrode preparation and battery assembly.

[0015] Furthermore, the doping of the low-valence molybdenum element is achieved by introducing a low-valence molybdenum source, which is a compound containing +3 valence molybdenum element, selected from at least one of MoCl3, MoBr3, MoI3, and Mo2O3.

[0016] Replacing traditional high-valence molybdenum sources with low-valence molybdenum sources can effectively avoid the problems of uncontrolled doping and uneven distribution caused by the volatilization of high-valence molybdenum sources during high-temperature calcination, making the actual doping amount precisely controllable and significantly improving doping uniformity. At the same time, this scheme does not require additional reduction treatment, simplifies the preparation process, and is conducive to large-scale industrial production.

[0017] Furthermore, the low-valence molybdenum source is Mo2O3.

[0018] Mo₂O₃, as a trivalent molybdenum source, exhibits high chemical stability and good dispersibility in solid-state reactions. The XRD diffraction peaks of the doped material show no impurities, indicating that Mo… 3+ It has successfully entered the crystal lattice to form a single solid solution.

[0019] Objective 2: A method for preparing a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, comprising the following steps: mixing lithium source, iron source, manganese source, phosphorus source and low-valence molybdenum source uniformly according to stoichiometric ratio, adding carbon source, and subjecting the mixture to ball milling, sand milling, spray drying, pre-calcination and high-temperature calcination to obtain the low-valence molybdenum-doped lithium manganese iron phosphate cathode material.

[0020] The preparation method provided by this invention involves mixing lithium, iron, manganese, phosphorus, and low-valence molybdenum sources in stoichiometric ratios and adding a carbon source. The mixture is then subjected to ball milling, sand milling, spray drying, pre-calcination, and high-temperature calcination, forming a coherent and controllable process route. The combination of ball milling and sand milling enables the nano-sizing of raw materials (D50≤500nm), providing a highly active precursor for subsequent solid-phase reactions. The spray drying process yields spherical precursor powder, which, after calcination, forms a "micro-nano composite" structure—the primary particle nano-size shortens the lithium-ion diffusion path, while the secondary micron-sized spherical particles improve tap density and slurry rheology. During high-temperature calcination, the carbon source undergoes in-situ pyrolysis to generate a uniform carbon coating layer, simplifying the process while ensuring effective coating.

[0021] Furthermore, the lithium source is selected from at least one of Li2CO3, LiOH·H2O, LiCH3COO and LiNO3; preferably Li2CO3.

[0022] Furthermore, the iron source is selected from at least one of Fe2O3, Fe3O4, FePO4 and FeC2O4; preferably FePO4.

[0023] Optimizing the combination of raw materials can reduce the introduction of impurities and improve the purity of the product phase.

[0024] Furthermore, the manganese source is selected from at least one of MnO2, Mn2O3, Mn3O4, MnCO3, and MnC2O4.

[0025] Furthermore, the phosphorus source is selected from at least one of LiH2PO4, (NH4)2HPO4 and H3PO4; preferably LiH2PO4 and a portion of the phosphate ions provided by FePO4.

[0026] Furthermore, the carbon source is selected from at least one of glucose, sucrose, citric acid, polyethylene glycol, and polyvinylpyrrolidone (PVP); preferably a sucrose + PVP composite.

[0027] Furthermore, the specific operation steps of the ball milling include: mixing each raw material according to the stoichiometric ratio and placing it in a ball milling jar, adding deionized water as a dispersant, and ball milling at a speed of 200~600 rpm for 4~12 hours.

[0028] Furthermore, the specific operation steps of the sand milling include: placing the ball-milled slurry in a nano-sand mill, using zirconia beads as the grinding media, and sand milling at a speed of 1000~2000 rpm to reduce the D-value of the particles in the slurry. 50 ≤500nm.

[0029] Furthermore, the specific operation steps of the spray drying include: introducing the slurry after sand milling into the spray drying tower, with an inlet temperature of 200~240℃ and an outlet temperature of 100~120℃, to obtain spherical precursor powder.

[0030] Furthermore, the specific operation steps of the pre-calcination include: heating the spray-dried precursor powder to 300-500°C at a heating rate of 1-10°C / min under an inert atmosphere, and holding at that temperature for 2-14 hours.

[0031] Furthermore, the specific operation steps of the high-temperature calcination include: heating the pre-calcined material to 600-800°C at a heating rate of 1-10°C / min under an inert or reducing atmosphere, and holding it at that temperature for 6-12 hours.

[0032] Furthermore, the inert atmosphere is selected from at least one of nitrogen, argon, and helium; the reducing atmosphere is a nitrogen / hydrogen mixture or an argon / hydrogen mixture, wherein the volume fraction of hydrogen is 1-10%. Here, " / " represents "and".

[0033] Furthermore, the amount of lithium source is adjusted to make the lithium element 2-7% more than the theoretical amount.

[0034] By precisely controlling the parameters of each process, the particle size distribution, morphological characteristics, and crystallinity of the product can be systematically regulated.

[0035] Third objective: A positive electrode sheet, the raw materials of which include the above-mentioned low-valence molybdenum-doped lithium manganese iron phosphate positive electrode material.

[0036] This positive electrode directly inherits the high capacity, excellent cycle stability, and high rate performance of the positive electrode material of this invention. Meanwhile, the material's unique micron-sized spherical morphology and high tap density facilitate electrode preparation processes such as slurry preparation, coating, and rolling, improving the consistency and yield of electrode processing and providing convenience for large-scale battery manufacturing.

[0037] Fourth objective: A lithium-ion battery in which the above-mentioned positive electrode sheet is included in the raw materials.

[0038] By employing the positive electrode sheet of this invention, the lithium-ion battery can fully leverage the 4.1V high-voltage platform of the positive electrode material to achieve higher energy density. Simultaneously, due to the effective suppression of the Jahn-Teller effect, structural degradation is slowed during long-term cycling, significantly extending cycle life. Excellent electronic conductivity and lithium-ion diffusion kinetics endow the battery with good rate performance, allowing it to maintain high capacity even at high-rate conditions such as 1C. Therefore, this lithium-ion battery can be widely used in electric vehicles, energy storage systems, portable electronic devices, and other electrical device fields with high requirements for energy density, cycle life, and rate performance, demonstrating promising market application prospects.

[0039] Fifth objective: The application of the aforementioned lithium-ion batteries in the field of electrical devices.

[0040] Compared with the prior art, the present invention has the following advantages and technical effects: (1) This invention uses low-valence molybdenum (Mo) 3+ ) doping, Mo 3+ The ionic radius (approximately 0.069 nm, six-coordinated) and Mn 2+ (0.067nm) and Fe 2+ (0.061nm) is closer, making it easier to enter the crystal lattice and occupy iron and / or manganese sites, resulting in better doping uniformity. Compared to high-valence molybdenum (Mo) 6+ Doping with low-valence molybdenum does not cause a drastic charge compensation effect, which is beneficial for maintaining the Mn content in the material. 3+ / Mn 2+ It has high redox activity and fully leverages the high voltage advantage of lithium manganese iron phosphate.

[0041] (2) Low price Mo 3+ Doping can effectively suppress Mn 3+ The Jahn-Teller effect. Mo 3+ The introduction of [a specific ingredient] can adjust the lattice parameters, reduce the distortion of the MnO6 octahedron, and enhance the stability of the crystal structure, thereby significantly improving the cycling performance of the material.

[0042] (3) Low price Mo 3+ Doping can reduce the band gap of materials and improve electronic conductivity; at the same time, the strong bond energy of Mo-O bonds is beneficial to widen the lithium-ion diffusion channels and improve the lithium-ion diffusion coefficient.

[0043] (4) This invention uses low-valence Mo 3+ Doping, such as with molybdenum sources (Mo2O3), avoids the problem of high-valence molybdenum sources (such as MoO3) being easily volatilized at high temperatures, and the doping amount is precisely controllable; at the same time, no additional reduction treatment is required, the preparation process is simple, and it is suitable for large-scale industrial production. Attached Figure Description

[0044] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 The X-ray diffraction patterns of the cathode materials prepared in Comparative Example 1, Example 1, and Example 2 are shown. Figure 2 A scanning electron microscope image of the cathode material prepared in Comparative Example 1; Figure 3 Here is a scanning electron microscope image of the cathode material prepared in Example 1; Figure 4 Comparison of the first charge-discharge curves of coin cells using the cathode materials prepared in Comparative Example 1, Comparative Example 2 and Example 1; Figure 5 Comparison of 1C charge-discharge curves of coin cells for the cathode materials prepared in Comparative Example 1, Comparative Example 2 and Example 1. Detailed Implementation

[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0046] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0047] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0048] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0049] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0050] This invention is implemented as follows: Firstly, this invention provides a low-valence molybdenum-doped lithium manganese iron phosphate cathode material with the general chemical formula: LiFe 1-x-y Mn x Mo y PO4 / C, where 0.3≤x≤0.7, 0.005≤y≤0.05, and x+y<1; preferably, 0.4≤x≤0.6, 0.005≤y≤0.03. The values ​​of x can be 0.40, 0.45, 0.50, 0.55, 0.585, 0.59, 0.595, 0.60, 0.65, 0.70, etc.; the values ​​of y can be 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, etc.

[0051] In cathode materials, molybdenum, in its lower valence state, exists as a +3 element, occupying some iron and / or manganese sites. 3+ The ionic radius is approximately 0.069 nm (six-coordinated), and it is compatible with Fe. 2+ (0.061nm), Mn 2+ The similar ionic radii (0.067nm) facilitate entry into the crystal lattice to form a substitutional solid solution, reducing lattice distortion.

[0052] The surface of the cathode material is coated with a carbon layer, and the mass percentage of the carbon layer is 1 to 10% of the total mass of the cathode material, preferably 3 to 7%. For example, in the following preferred embodiments of the present invention, the mass percentage of the carbon layer is 5% of the total mass of the cathode material.

[0053] Secondly, this invention provides a method for preparing a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, comprising the following steps: (1) Mix lithium source, iron source, manganese source, phosphorus source and trivalent molybdenum source according to stoichiometric ratio, add carbon source, add deionized water as solvent, place in ball mill jar and ball mill at 200~600 rpm (e.g. 600 rpm) for 4~12 h (e.g. 6 h) to obtain slurry; (2) Place the ball-milled slurry in a nano-grinding mill, using zirconia beads as the grinding media, and mill at a speed of 1000~2000 rpm (e.g., 1000 rpm) to reduce the particle size of the slurry. 50 ≤500nm; (3) The slurry after sand milling is introduced into the spray drying tower with an inlet temperature of 200~240℃ (e.g., 200℃) and an outlet temperature of 100~120℃ (e.g., 110℃) to obtain spherical precursor powder; (4) The precursor powder is heated to 300-500℃ (e.g., 450℃) at a heating rate of 1-10℃ / min (e.g., 2℃ / min) under an inert atmosphere and held for 2-6h (e.g., 4h) for precalcination. (5) The pre-calcined material is heated to 600-800℃ (e.g., 650℃, 700℃ or 750℃) at a heating rate of 1-10℃ / min (e.g. 2℃ / min) under an inert or reducing atmosphere, and held at that temperature for 6-12h (e.g. 10h) for high-temperature calcination. It is then naturally cooled to room temperature to obtain a low-valence molybdenum-doped lithium manganese iron phosphate cathode material.

[0054] In some alternative embodiments, in step (1): The lithium source is selected from at least one of Li2CO3, LiOH·H2O, LiCH3COO and LiNO3, with Li2CO3 being preferred.

[0055] The iron source is selected from at least one of Fe2O3, Fe3O4, FePO4 and FeC2O4, with FePO4 being preferred.

[0056] The manganese source is selected from at least one of MnO2, Mn2O3, Mn3O4, MnCO3 and MnC2O4, with Mn3O4 being preferred.

[0057] The phosphorus source is selected from at least one of LiH2PO4, (NH4)2HPO4 and H3PO4, with LiH2PO4 being preferred.

[0058] The trivalent molybdenum source is selected from at least one of MoCl3, MoBr3, MoI3 and Mo2O3, preferably Mo2O3 or MoCl3. The advantages of using a trivalent molybdenum source are: (1) Mo 3+ (1) It can directly enter the crystal lattice without additional reduction treatment; (2) It avoids the problem that high-priced molybdenum sources (such as MoO3) may volatilize at high temperatures; (3) The process is simple and the cost is low.

[0059] The carbon source is selected from at least one of glucose, sucrose, citric acid, polyethylene glycol, and PVP, preferably sucrose or a mixture of sucrose and PVP (mass ratio of 5:1). The carbon source decomposes during high-temperature calcination to generate carbon, which coats the material surface and improves the material's electronic conductivity.

[0060] By adjusting the amount of lithium source used, the lithium element is made to be 1-10% more than the theoretical amount, preferably 3-5% more (e.g., 5%), to compensate for the loss of lithium volatilization during high-temperature calcination.

[0061] In some alternative embodiments, in step (4): The pre-calcination temperature can be 300℃, 350℃, 400℃, 450℃, 500℃, etc., preferably 450℃; the holding time can be 2h, 3h, 4h, 5h, 6h, etc., preferably 4h. The purpose of pre-calcination is to remove moisture and organic matter from the precursor, and at the same time allow the raw materials to react initially.

[0062] In some alternative embodiments, in step (5): The high-temperature calcination temperature can be 600℃, 650℃, 700℃, 750℃, 800℃, etc., with 700℃ being preferred; the holding time can be 6h, 8h, 10h, 12h, 16h, 20h, 24h, etc., with 10h being preferred. High-temperature calcination allows all raw materials to react fully, forming lithium manganese iron phosphate with an olivine structure.

[0063] The inert atmosphere is selected from at least one of nitrogen, argon, or helium, with nitrogen being preferred; the reducing atmosphere is a nitrogen / hydrogen mixture or an argon / hydrogen mixture, wherein the volume fraction of hydrogen is 1-10%, preferably 3-5%. A reducing atmosphere is beneficial for preventing Mn from entering the atmosphere. 2+ Oxidized to Mn 3+ At the same time, it helps maintain Mo 3+ The low price state.

[0064] This invention also provides a positive electrode sheet, comprising the low-valence molybdenum-doped lithium manganese iron phosphate positive electrode material prepared according to this invention. The positive electrode sheet may further include a positive current collector, on which a positive active coating is formed.

[0065] This invention also provides a lithium-ion battery, including the above-mentioned positive electrode, and may further include a negative electrode, electrolyte, separator, etc.

[0066] This invention also provides an electrical device including the aforementioned lithium-ion battery.

[0067] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.

[0068] All raw materials used in this invention were purchased from the market.

[0069] The technical solution of the present invention will be further illustrated by the following embodiments.

[0070] Example 1 A method for preparing a low-valence molybdenum-doped lithium manganese iron phosphate cathode material, the target material having the chemical formula LiFe 0.4 Mn 0.59 Mo 0.01 PO4 / C (i.e., x=0.59, y=0.01), with a carbon content of 5% of the total mass of the target material, the specific steps are as follows: S1: Weigh Li2CO3 (lithium ratio of 1:1.05, i.e., lithium element is 5% in excess of the theoretical amount), FePO4, MnCO3, LiH2PO4 and Mo2O3 according to the stoichiometric ratio, and carbon source (sucrose and PVP mixed in a mass ratio of 5:1) accounting for 5% of the total mass of the theoretical product. Place the resulting mixture in a ball mill jar, use deionized water as a dispersant, add deionized water according to the ratio of mixture to dispersant of 40g:120mL, and ball mill at 600rpm for 6h to obtain a slurry. S2: Place the ball-milled slurry in a nano-grinding mill, using zirconia beads as the grinding media, and mill at a speed of 1000 rpm to reduce the particle size (D) of the slurry. 50 ≤500nm; S3: The slurry after sand milling is introduced into a spray drying tower with an inlet temperature of 200℃ and an outlet temperature of 110℃ to obtain spherical precursor powder; S4: Place the precursor powder in a tube furnace and heat it to 450°C at a heating rate of 2°C / min under a nitrogen atmosphere, and hold it at that temperature for 4 hours for pre-calcination. S5: The pre-calcined material is heated to 700℃ at a heating rate of 2℃ / min under a pure nitrogen atmosphere and held at that temperature for 10h for high-temperature calcination. After naturally cooling to room temperature, it is subjected to airflow pulverization to obtain low-valence molybdenum-doped lithium manganese iron phosphate cathode material.

[0071] Example 2 Same as Example 1, except that in step S1, the amount of Mo2O3 used makes the chemical formula of the target material LiFe. 0.4 Mn 0.595 Mo 0.005 PO4 / C (i.e. x=0.595, y=0.005).

[0072] Example 3 Same as Example 1, except that in step S1, the amount of Mo2O3 used makes the chemical formula of the target material LiFe. 0.4 Mn 0.585 Mo 0.015 PO4 / C (i.e. x=0.585, y=0.015).

[0073] Example 4 Same as Example 1, except that in step S5, the calcination temperature is 650°C.

[0074] Example 5 Same as Example 1, except that in step S5, the calcination temperature is 750°C.

[0075] Example 6 Same as Example 1, except that in step S1, the carbon source is sucrose alone, that is, sucrose accounting for 5% of the total mass of the theoretical product is added.

[0076] Example 7 Same as Example 1, except that in step S1, Mo2O3 is replaced with MoCl3 according to the stoichiometric ratio.

[0077] Example 8 Same as Example 1, except that in step S5, the volume fraction of hydrogen in the nitrogen / hydrogen mixture is 5%.

[0078] Comparative Example 1 A method for preparing lithium manganese iron phosphate cathode material without low-valence molybdenum doping, the target material having the chemical formula LiFe 0.4 Mn 0.6 PO4 / C, the specific steps are as follows: S1: Weigh Li2CO3 (lithium ratio 1:1.05), FePO4, MnCO3, NH4H2PO4, and sucrose accounting for 5% of the total mass of the theoretical product according to the stoichiometric ratio. Place the resulting mixture in a ball mill jar and add deionized water at a ratio of 40g:120mL. Ball mill at 600rpm for 6h. S2~S5: Same as in Example 1, to obtain lithium iron phosphate cathode material without low-valence rare metal molybdenum doped.

[0079] Comparative Example 2 A method for preparing a high-valence molybdenum-doped lithium manganese iron phosphate cathode material, the target material having the chemical formula LiFe 0.4 Mn 0.59 Mo 0.01 PO4 / C (using Mo) 6+ Doping (i.e., x=0.59, y=0.01) involves the following steps: S1: Weigh out Li2CO3 (lithium ratio 1:1.05), FePO4, MnCO3, NH4H2PO4 and MoO3 (Mo 6+ The mixture was prepared by adding sucrose (5% of the total mass of the theoretical product) to a ball mill jar, using deionized water as a dispersant, and adding deionized water at a ratio of 40g:120mL. The mixture was then ball-milled at 600rpm for 6 hours to obtain a slurry. S2~S5: Same as in Example 1, to obtain high-valence molybdenum-doped lithium manganese iron phosphate cathode material.

[0080] Performance testing Test method: The positive electrode material powders prepared in Examples 1-7 and Comparative Examples 1-2 were thoroughly mixed with polyvinylidene fluoride and conductive carbon black at a mass ratio of 8:1:1. After stirring into a homogeneous slurry, the mixture was coated onto aluminum foil, dried in a vacuum drying oven at 80°C, rolled, and cut into circular positive electrode sheets. Using lithium metal sheets as the negative electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 / EC+DMC (volume ratio 1:1) as the electrolyte, 2016 coin cells were assembled in a glove box filled with argon atmosphere and placed in a battery test cabinet at a constant temperature of 25°C for charge-discharge testing.

[0081] Table 1. Electrochemical performance of the cathode materials prepared in Examples 1-7 and Comparative Examples 1-2 The results in Table 1 show that: (1) Mo 3+ Doping effect on capacity improvement: Comparing Example 1 and Comparative Example 1, at a rate of 0.1C, Mo 3+ After doping, the discharge specific capacity increased from 144.33 mAh / g to 166.04 mAh / g, an increase of 15.0%; at 1C rate, it increased from 109.02 mAh / g to 130.70 mAh / g, an increase of 19.9%. This indicates that Mo... 3+ Doping effectively improves the electronic conductivity and lithium-ion diffusion kinetics of the material, enabling the active material to participate more fully in the electrochemical reaction at high rates.

[0082] (2) Mo 3+ with Mo 6+ Comparison of doping effects: Comparing Example 1 and Comparative Example 2 (both with the same stoichiometry and molybdenum doping amount y=0.01, differing only in the valence state of the molybdenum source), Example 1 showed a 15.66 mAh / g higher 0.1C discharge capacity (166.04 mAh / g) and a 10.99 mAh / g higher 1C discharge capacity (130.70 mAh / g vs 119.71 mAh / g) compared to Comparative Example 2 (150.38 mAh / g). The first-cycle efficiency (95.72% vs 95.68%) was essentially the same. This result fully demonstrates that, under the same doping conditions, low-valence Mo... 3+ Doping significantly improves electrochemical performance compared to high-valence Mo. 6+ Doping. The fundamental reason is: (a) Mo 3+ The ionic radius (0.069 nm) and Mn 2+ / Fe2+ (b) Mo 3+ Doping does not produce a drastic charge compensation effect and will not affect Mn. 3+ Restored to Mn 2+ Thus, Mn was completely preserved. 3+ / Mn 2+ (c) Mo 3+ (4d) 3 ) and Mn 3+ (3d) 4 The superexchange interactions between the two can synergistically suppress Jahn-Teller distortion, while Mo 6+ (4d) 0 It does not have unpaired electrons and cannot produce a similar effect.

[0083] (3) Optimization of doping amount: Comparing Example 1 (y=0.01), Example 2 (y=0.005), and Example 3 (y=0.015), the material exhibited the best 0.1C discharge capacity (166.04 mAh / g) and 1C discharge capacity (130.70 mAh / g) when the doping amount was too low (y=0.005). 3+ The suppression of the Jahn-Teller effect is insufficient, resulting in limited capacity improvement. When the doping concentration is too high (y=0.015), excessive inactive ions occupy transition metal sites, potentially diluting the redox activity of Mn / Fe and introducing excessive lattice defects, thus hindering lithium-ion diffusion. This indicates that Mo... 3+ There is an optimal dosage effect in doping, and y=0.01 is the preferred solution in this invention.

[0084] (4) Effect of calcination temperature: Comparing Example 1 (700℃), Example 4 (650℃), and Example 5 (750℃), the sample calcined at 700℃ exhibited the best 1C rate performance (130.70 mAh / g). The sample calcined at 650℃ had a relatively low 0.1C discharge capacity (150.62 mAh / g), possibly due to insufficient crystallinity, but it had the highest first-cycle efficiency (96.76%), indicating fewer interfacial side reactions at lower temperatures. The sample calcined at 750℃ (154.55 mAh / g) had a capacity between the two, but excessively high temperatures could lead to excessive grain growth, partially destroying the spherical morphology formed by spray granulation, and resulting in higher energy consumption. Overall, 700℃ is the optimal calcination temperature that balances capacity utilization, rate performance, and energy consumption.

[0085] (5) Effect of carbon source and molybdenum source: Comparing Example 1 (sucrose + PVP composite carbon source), Example 6 (sucrose alone) and Example 7 (MoCl3 molybdenum source), Example 1, which uses a composite carbon source, has a better 1C discharge capacity (130.70 mAh / g) than Example 6, which uses sucrose alone (108.01 mAh / g), indicating that the introduction of PVP enhances the density and conductivity of the carbon layer; Example 1, which uses Mo2O3 as the molybdenum source, has a better 0.1C discharge capacity (166.04 mAh / g) than Example 7, which uses MoCl3 (162.27 mAh / g), which may be related to the higher chemical stability and more uniform dispersion of Mo2O3 in solid-phase reactions.

[0086] Figure 1 The X-ray diffraction (XRD) patterns of the cathode materials prepared in Comparative Example 1, Example 1, and Example 2 are shown. As can be seen from the patterns, all diffraction peaks of the three samples are in good agreement with the standard card of olivine-structured lithium manganese iron phosphate, with space group Pnma. Furthermore, no characteristic peaks of molybdenum-related impurity phases (such as characteristic peaks of MoO3, Mo2O3, or MoP) were observed, indicating that Mo... 3+ Mo has been successfully doped into the LMFP lattice to form a single solid solution, rather than existing as a physical mixture or surface attachment. The undoped sample in Comparative Example 1 exhibits a pure olivine phase; the sharp peaks and narrow full width at half maximum (FWHM) of the diffraction peaks in Examples 1 (y=0.01) and 2 (y=0.005) indicate that Mo... 3+ The doping did not disrupt the main crystal structure of the material, and the material's crystallinity remained good. XRD results confirmed that the trivalent molybdenum source (Mo2O3) used in this invention can effectively enter the transition metal sites in the LMFP lattice during solid-state calcination, forming a uniform substitutional solid solution, which provides a structural basis for subsequent improvement of electrochemical performance.

[0087] Figure 2 Here is a scanning electron microscope (SEM) image of the cathode material prepared in Comparative Example 1, from... Figure 2 It can be seen that the primary particle morphology of the undoped sample (Comparative Example 1) is irregular, the size distribution is wide (about 200-400nm), there is obvious agglomeration between particles, and the surface is relatively rough, which is not conducive to the dispersion of slurry and electrode processing during homogenization.

[0088] Figure 3 The image shown is a scanning electron microscope (SEM) image of the cathode material prepared in Example 1. Figure 3 It can be clearly seen that after spray drying granulation and Mo 3+ The doped sample (Example 1) formed micron-sized secondary particles with high sphericity (D 50These secondary particles, approximately 2-3 μm in size, are composed of a large number of nanoscale primary particles (approximately 200-300 nm) tightly packed together, exhibiting typical "micro-nano composite" structural characteristics. The nanoscale size of the primary particles ensures the shortening of the lithium-ion diffusion path (shortening the diffusion path helps overcome the kinetic limitations of the one-dimensional diffusion channels in the olivine structure), while the spherical morphology of the secondary particles is beneficial for improving the tap density of the powder, enhancing the rheological properties of the slurry, and improving the processing performance of the electrode. A uniform carbon coating layer is visible on the particle surface, which is generated by the in-situ pyrolysis of sucrose and PVP during high-temperature calcination, effectively improving the electronic contact between particles and reducing the interfacial contact impedance. Compared with Comparative Example 1, the particle morphology of Example 1 is more regular and the size distribution is more concentrated, mainly due to the effective control of the secondary particle morphology by the spray drying process. Good particle morphology is an important guarantee for achieving high tap density and excellent electrochemical performance in materials.

[0089] Figure 4 Comparison of the first charge-discharge curves (0.1C rate, voltage window 2~4.5V) of coin cells using the cathode materials prepared in Comparative Example 1, Comparative Example 2, and Example 1. Two characteristic voltage plateaus can be clearly distinguished from the graphs: approximately 3.4V corresponds to Fe... 2+ / Fe 3+ The redox reaction, approximately 4.1V corresponds to Mn 2+ / Mn 3+ The redox reaction is a typical dual-plateau charge-discharge characteristic of LMFP materials. The undoped sample in Comparative Example 1 shows a significantly smaller capacity contribution in the 4.1V manganese plateau region (only about 65-70 mAh / g), indicating that Mn... 2+ / Mn 3+ The reaction kinetics were hampered by the Jahn-Teller effect. In contrast, Mo in Example 1... 3+ The 4.1V manganese plateau in the doped sample (y=0.01) is flatter and lasts longer (contributing approximately 85~90 mAh / g), indicating that Mo... 3+ Doping effectively suppressed the negative impact of Jahn-Teller distortion on reaction kinetics, Mn 2+ / Mn 3+ The reversibility and kinetics of the reaction were significantly improved. Comparative Example 2: Mo 6+ The 4.1V plateau of the doped sample (y=0.01) falls between the two (contributing approximately 75-80 mAh / g), significantly inferior to Mo. 3+ Doped samples. Based on the capacity data at 0.1C, the discharge specific capacity of Example 1 (166.04 mAh / g) was increased by 15.0% compared to Comparative Example 1 (144.33 mAh / g) and by 10.4% compared to Comparative Example 2 (150.38 mAh / g), fully demonstrating the effectiveness of low-valence Mo.3+ Doping has a significant effect on realizing the capacity potential of materials.

[0090] Figure 5 Comparison of 1C charge-discharge curves (voltage window 2.0~4.5V) of the cathode materials prepared in Comparative Example 1, Comparative Example 2, and Example 1 at coin cell rates. The graphs clearly show significant differences in capacity performance and polarization characteristics among the three samples at 1C. The undoped sample of Comparative Example 1 exhibits a discharge specific capacity of only 109.02 mAh / g at 1C, and has the largest voltage gap (polarization voltage) between the charge-discharge curves. This is due to its extremely low intrinsic electronic conductivity (102 mAh / g). -9 ~10 -11 The reaction kinetics lag caused by the Jahn-Teller effect (S / cm) and the sharp increase in polarization at high rates prevents the capacity from being fully utilized. Comparative Example 2: Mo 6+ The 1C discharge specific capacity of the doped sample increased to 119.71 mAh / g, but its effect on suppressing and improving the Jahn-Teller effect was limited. In contrast, the Mo in Example 1... 3+ The doped sample exhibits a high 1C discharge specific capacity of 130.70 mAh / g, representing a 19.9% ​​improvement over Comparative Example 1 and a 9.2% improvement over Comparative Example 2, with the lowest polarization voltage between the charge and discharge curves. These results demonstrate the effectiveness of the low-valence Mo proposed in this invention. 3+ The doping strategy has significant polarization suppression and capacity enhancement effects under high-rate conditions.

[0091] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A low-valence molybdenum-doped lithium manganese iron phosphate cathode material, characterized in that, The general chemical formula of the cathode material is: LiFe 1-x-y Mn x Mo y PO4 / C, wherein the low-valence molybdenum exists in the material in the form of +3 valence; 0.3≤x≤0.7, 0.005≤y≤0.05; the surface of the cathode material is coated with a carbon layer; in the cathode material, molybdenum ions occupy part of the iron sites and / or manganese sites.

2. The low-valence molybdenum-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, In the general chemical formula, 0.4 ≤ x ≤ 0.6, 0.005 ≤ y ≤ 0.

03.

3. The low-valence molybdenum-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The mass of the carbon layer is 1 to 10% of the total mass of the cathode material.

4. The low-valence molybdenum-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The doping of low-valence molybdenum is achieved by introducing a low-valence rare metal molybdenum source, which is a compound of +3 valence molybdenum, selected from at least one of MoCl3, MoBr3, MoI3, and Mo2O3.

5. The low-valence molybdenum-doped lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The low-valence molybdenum source is Mo2O3.

6. A method for preparing a low-valence molybdenum-doped lithium manganese iron phosphate cathode material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Lithium source, iron source, manganese source, phosphorus source and low-valence molybdenum source are mixed evenly according to stoichiometric ratio, carbon source is added, and the mixture is ball-milled, sand-milled, spray-dried, pre-calcined and calcined at high temperature to obtain low-valence molybdenum-doped manganese iron phosphate cathode material.

7. The preparation method according to claim 6, characterized in that, The lithium source is selected from at least one of Li2CO3, LiOH·H2O, LiCH3COO, and LiNO3; The iron source is selected from at least one of Fe2O3, Fe3O4, FePO4 and FeC2O4; The manganese source is selected from at least one of MnO2, Mn2O3, Mn3O4, MnCO3, and MnC2O4; The phosphorus source is selected from at least one of LiH2PO4, (NH4)2HPO4 and H3PO4; The carbon source is selected from at least one of glucose, sucrose, citric acid, polyethylene glycol, and polyvinylpyrrolidone.

8. The preparation method according to claim 6, characterized in that, The specific operation steps of the ball milling include: mixing each raw material according to the stoichiometric ratio and placing it in a ball milling jar, adding deionized water as a dispersant, and ball milling at a speed of 200~600 rpm for 4~12 hours; The specific operation steps of the sand milling include: placing the ball-milled slurry in a nano-sand mill, using zirconia beads as the grinding media, and milling at a speed of 1000~2000 rpm to reduce the particle size (D) of the slurry. 50 ≤500nm; The specific operation steps of the spray drying include: introducing the slurry after sand milling into the spray drying tower, with an inlet temperature of 200~240℃ and an outlet temperature of 100~120℃, to obtain spherical precursor powder; The specific operation steps of the pre-calcination include: heating the spray-dried precursor powder to 300-500°C at a heating rate of 1-10°C / min under an inert atmosphere, and holding it at that temperature for 2-14 hours. The specific operation steps of the high-temperature calcination include: heating the pre-calcined material to 600-800℃ at a heating rate of 1-10℃ / min under an inert or reducing atmosphere, and holding it at that temperature for 6-12 hours.

9. A positive electrode sheet, characterized in that, The raw materials include the low-valence molybdenum-doped lithium manganese iron phosphate cathode material as described in any one of claims 1 to 5.

10. A lithium-ion battery, characterized in that, The raw materials include the positive electrode sheet as described in claim 9.